A73 PHARYNGEAL VARICES AS A COMPLICATION OF PORTAL HYPERTENSION: A CASE SERIES - Ghaith, J (J Can Assoc Gastroenterol, 2020)
BACKGROUND: One of the complications of portal hypertension, with or without the presence of cirrhosis, is the development of varices along the length of the gastrointestinal tract. The commonest sites are along the esophagus or in the stomach. Ectopic varices in the small and large bowels can also be observed, but ectopic varices in the pharynx are extremely uncommon. AIMS: To present a case series and review the literature regarding pharyngeal varcies. METHODS: - RESULTS: Three elderly female patients presented for esophagogastric varices surveillance gastroscopy were diagnosed with pharyngeal varices. One patient has hepatitis C cirrhosis, while the other two non-cirrhotic patients have myeloproliferative neoplasm (MPN). None of the patients had thromboses of the portal vein or its tributaries. All three patient have concomitant esophageal varices, but only one required band ligation of her esophageal varices. All patients are asymptotic except for mild dysphagia. No patient has bled from their pharyngeal varices to date. Two patients have had prophylactic treatment of their portal hypertension with non-selective beta blocker (NSBB), while the third one has not received NSBB prophylaxis because of her age. CONCLUSIONS: Pharyngeal varices are extremely rare. To date, there are three case reports in the literature, however, we have been able to identify three cases in our practice. The previous two cases reported possible left-sided portal hypertension with splenic vein thrombosis, leading to the development of collateral vessels including a gastrocaval shunt, which by some contiguous route connects to the brachiocephalic vein; and a third case was a complication of neck dissection surgery. In our case series, none of our patients had splenic vein thrombosis. However, none of them has had a careful CT angiogram to delineate the portal vein tributaries and the collateral vessels, which may further help to define their pathogenesis. It is unclear whether NSBB would be effective as primary prophylaxis against their bleeding, The plan is to continue to monitor these patients to learn about the natural history of these pharyngeal varices. FUNDING AGENCIES: None